Physiological Response of Lactobacillus plantarum to Salt and Nonelectrolyte Stress - Glaasker, Erwin (American Society for Microbiology, 1998)
In this report, we compared the effects on the growth of Lactobacillus plantarum of raising the medium molarity by high concentrations of KCl or NaCl and iso-osmotic concentrations of nonionic compounds. Analysis of cellular extracts for organic constituents by nuclear magnetic resonance spectroscopy showed that salt-stressed cells do not contain detectable amounts of organic osmolytes, whereas sugar-stressed cells contain sugar (and some sugar-derived) compounds. The cytoplasmic concentrations of lactose and sucrose in growing cells are always similar to the concentrations in the medium. By using the activity of the glycine betaine transport system as a measure of hyperosmotic conditions, we show that, in contrast to KCl and NaCl, high concentrations of sugars (lactose or sucrose) impose only a transient osmotic stress because external and internal sugars equilibrate after some time. Analysis of lactose (and sucrose) uptake also indicates that the corresponding transport systems are neither significantly induced nor activated directly by hyperosmotic conditions. The systems operate by facilitated diffusion and have very high apparent affinity constants for transport (>50 mM for lactose), which explains why low sugar concentrations do not protect against hyperosmotic conditions. We conclude that the more severe growth inhibition by salt stress than by equiosmolal concentrations of sugars reflects the inability of the cells to accumulate K(+) (or Na(+)) to levels high enough to restore turgor as well as deleterious effects of the electrolytes intracellularly.